Confessions of an Agnostic: Apologia Pro Vita Sua - Ruse, Michael (Sophia, 2021)
Francis Collins, the director of the NEH and well-known Christian, has said that agnosticism is a bit of a cop-out. Either be a Christian or be an atheism, but have the guts to make up your mind. I shall argue in a positive way for agnosticism, showing that it can be as vibrant a position as belief or non-belief. It gives you a renewed appreciation of life and the world in which we live.